Review On Layered Double Hydroxide Materials For Environment Sustainability Applications (International Journal of Environmental Sciences, 2025)
Layered double hydroxides (LDHs) are a class of tunable, brucite-like clays composed of mixed metal hydroxides and interlayer anions. Their unique structure—positively charged metal hydroxide layers balanced by exchangeable interlayer anions—endows LDHs with high anion exchange capacity, surface basicity, and reusability. These properties make LDHs promising for environmentally sustainable applications, ranging from carbon dioxide (CO₂) capture to water purification. In this review, we present an updated overview of LDH characterization techniques (XRD, FTIR, electron microscopy, thermal analysis) that confirm structure and composition. We then compare major synthesis methods (co-precipitation, hydrothermal, sol–gel, and urea homogeneous precipitation), highlighting how preparation routes influence LDH properties. A detailed discussion of LDH applications in environmental sustainability follows, focusing on CO₂ adsorption for greenhouse gas mitigation and the removal of pollutants (heavy metals, dyes, and oxyanions) from water via adsorption, ion exchange, and catalytic degradation processes. The high sorption capacities of LDHs (often hundreds of mg/g for contaminants) and their “memory effect” regeneration by calcination–rehydration cycles are emphasized. LDH Characterization is discussed prior to synthesis to underscore how analytical insights guide optimal preparation. Overall, LDHs emerge as versatile, recyclable, and non-toxic materials aligning with green chemistry principles. Future research directions for enhancing LDH performance (e.g., functionalization, composite formation) and scaling up for real-world environmental remediation are also outlined.